Findings at endoscopic retrograde cholangiopancreatography after endoscopic treatment of postcholecystectomy bile leaks - Azar, Riad (2010)
Background Although the endoscopic management of bile leaks after cholecystectomy (CCY) is well established, the yield of a routine endoscopic retrograde cholangiogram (ERC) with a bile duct sweep at the time of stent removal is unclear. This study aimed to describe the prevalence of abnormal findings at follow-up ERC to determine whether upper endoscopy with stent removal and without cholangiography would suffice. Methods A retrospective cohort analysis of all patients referred for initial and follow-up ERC with post-CCY bile leak was performed. The rate of abnormal findings was measured including choledocholithiasis, biliary strictures, and persistent bile leaks at follow-up ERC. Secondarily, the study sought to define the clinical characteristics of patients who demonstrated stones or sludge at follow-up assessment. Results Between January, 2003 and April, 2008, 105 patients underwent initial and follow-up ERC. After a mean interval of 6.9 ± 2.7 weeks between endoscopies, 29 (27.6%) of the 105 patients demonstrated one or more abnormalities including persistent bile leak (n = 8), common bile duct (CBD) stones (n = 12), and CBD sludge alone (n = 9). In the subgroup analysis of the patients who underwent a balloon sweep at initial and follow-up ERC, the prevalence of CBD stones or sludge at the follow-up ERC was 17.6%. Besides stones during the initial ERC, no significant clinical predictors of CBD stones were found at follow-up ERC including surgical approach, interval between endoscopies, and location of bile leak. Conclusion After endoscopic treatment of a bile leak, the prevalence of abnormalities at follow-up ERC is significant. A repeat cholangiogram with a balloon sweep is preferred at the time of stent removal.